Calcitonin measurement in aspiration needle washout fluids has higher sensitivity than cytology in detecting medullary thyroid cancer: a retrospective multicentre study. (20th May 2013) - Trimboli, Pierpaolo; Cremonini, Nadia; Ceriani, Luca; Saggiorato, Enrico; Guidobaldi, Leo; Romanelli, Francesco; Ventura, Claudio; Laurenti, Oriana; Messuti, Ilaria; Solaroli, Erica; Madaio, Raffaele; Bongiovanni, Massimo; et al.
Summary Objective Only few studies analysed the capability of cytology in detecting medullary thyroid cancer (MTC), and they reported a low accuracy of this diagnostic technique. Recently, calcitonin (CT) measurement in aspiration needle washout (FNA‐CT) of thyroid and neck lesions has been reported as a sensitive tool for MTC. The aim of this study is to compare the sensitivity of FNA‐CT and cytology in detecting MTC and to assess a cut‐off value of FNA‐CT for clinical practice. Patients Thirty‐eight MTC lesions from 36 patients were retrospectively studied, diagnosed and treated in four different centres. Furthermore, 52 nonmedullary lesions from subjects undergone biopsy following increased serum CT were collected as a control group. Results Cytology detected MTC in 21/37 lesions with 56·8% sensitivity. The median FNA‐CT value was 2000 pg/ml (range 58–10 000 pg/ml) in MTC and 2·7 pg/ml (range <2–13 pg/ml) in controls (P < 0·001). Using a cut‐off of 39·6 pg/ml, MTC lesions could be identified with 100% sensitivity and specificity. As the most important finding, 14 histologically proved MTC lesions could be detected by FNA‐CT, despite they were cytologically diagnosed as benign or nonconclusive. Conclusions This study shows, as the first in a multicentre series, that FNA‐CT sensitivity is higher than that of cytology in diagnosing MTC. To avoid false‐negative MTC by cytology, CT measurement in aspiration needle washout is to be performed in all patients undergoing biopsy following high serum CT.